God, Grievance and Greed: War in Cabo Delgado, Mozambique - Bonate, Liazzat J. K.; Israel, Paolo; Rosario, Carmeliza (Kronos (Bellville, South Africa), 2024)
In 2017 a 'new war', characterised as a jihadist insurgency, erupted in the northerly Mozambican province of Cabo Delgado.The war began in the context of the discovery of new natural resources, the setting up of transnational extractive industries and of an economic crisis generated by the 'hidden debt' scandal. Harsh military responses from the Mozambican government and international actors - SADC and Rwanda especially - have not halted the insurgency, which has dramatically expanded, especially since the insurgents declared their allegiance to the Islamic State (IS) in 2019, causing massive internal displacement of the civil population. This article is an introduction to the special issue, God, Grievance and Greed: War in Cabo Delgado (Mozambique), which aims to bring historical and ethnographic depth to the study of this conflict. The issue draws together a series of layered interventions reflecting the multi-faceted nature of the events, as well as their social and human dimensions, without silencing the voices of the people involved. This introduction serves to frame those interventions, establishing a broad chronology of the conflict; provide an overview of the complex history of Cabo Delgado; discuss the literature produced so far on the insurgency; and locate the events in Cabo Delgado at the interface between local dynamics - capitalist extraction, the erosion of democratic processes, youth marginalisation, ethnic conflict - and global jihadism.